2013
DOI: 10.2478/arsm-2013-0012
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics of the aortic arch organization

Abstract: Our study was performed on 228 cases by dissection, by plastic injection followed by corrosion or dissection and by simple and CT angiography study. Each morphological aspect was assessed on a different numbers of cases, as long as the same case could not provide data on all studied elements. We assessed: the number of branches that originate from the aortic arch, the level of origin and the morphological type of the aortic arch. In terms of number of branches emerging from the aortic arch, most commonly are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Another cadaveric study of 25 Korean cadavers found the direct origin of the left vertebral artery in 8% of cases, and 8% of 75 Indian cadavers also exhibited this variation [13,29]. The highest incidence of direct origin of the left vertebral artery in Anatomical and radiological evaluation of the variation in the branching patterns and morphology of the aortic arch in the irish population-A morphometric study the literature was 13.3% in a cadaveric and radiological study of Romanian individuals [30].…”
Section: Tablementioning
confidence: 99%
“…Another cadaveric study of 25 Korean cadavers found the direct origin of the left vertebral artery in 8% of cases, and 8% of 75 Indian cadavers also exhibited this variation [13,29]. The highest incidence of direct origin of the left vertebral artery in Anatomical and radiological evaluation of the variation in the branching patterns and morphology of the aortic arch in the irish population-A morphometric study the literature was 13.3% in a cadaveric and radiological study of Romanian individuals [30].…”
Section: Tablementioning
confidence: 99%